New Possibilities of Antibiotic Therapy for Blepharoconjunctivitis in Children - E. L. Efimova; V. V. Brzheskiy (Oftalʹmologiâ, 2021)
The problem of drug therapy for bacterial eye infections in children has remained relevant for many years. The greatest interest of ophthalmologists in recent years is associated with the use of fluoroquinolones in the treatment of inflammatory eye diseases of the bacterial etiology. At the same time, new ophthalmic dosage forms of fluoroquinolones that have appeared in recent years naturally require additional research on their effectiveness.Objective: to study the clinical efficacy of the antibacterial drug Oftocypro (0.3 % cyprofloxacin in ophthalmic ointment) in the treatment of chronic blepharoconjunctivitis in children.Materials. The study involved 38 children aged 3 to 18 years (mean age 10.3 ± 2.7 years) with clinical manifestations of blepharoconjunctivitis. All patients were divided into 2 groups of equal size: 18 children (36 eyes) — with bacterial blepharoconjunctivitis and 20 (40) — with chlamydial blepharoconjunctivitis. The diagnosis was verified based on the clinical picture of blepharoconjunctivitis and laboratory data: detection of pathogenic microflora in the conjunctival cavity of patients of the first group and chlamydia antigen — in epithelial cells in scraping material from the conjunctiva by immunohistochemical analysis.Results. The analysis of the data obtained during the examination and treatment of children with blepharoconjunctivitis of bacterial etiology (group I), a reliable dynamics of controlled clinical and laboratory parameters was established. There was a significant positive dynamics of all controlled parameters of the clinical course of chronic bacterial blepharoconjunctivitis against the background of the drug Oftocipro ophthalmic ointment 0.3 % use. All children with chronic chlamydial blepharoconjunctivitis with the background of treatment with Oftocypro, ophthalmic ointment 0.3 %, showed a steady tendency towards relief of the estimated clinical signs of the disease. According to the results of laboratory studies, it was found that on the 28th day of treatment with Oftocypro chlamydia in the cells of the epithelium of the conjunctiva was re-detected in 4 out of 20 patients (20 %).Conclusion. The high efficacy of the drug Oftocypro ophthalmic ointment 0.3 %, in combination with the absence of pronounced side effects, makes it possible to recommend this drug for wider practical use.